Proving the correct execution of concurrent services in zero-knowledge - Setty, Srinath; Angel, Sebastian; Gupta, Trinabh; Lee, Jonathan (Symposium on Operating Systems Design and Implementation (OSDI), 2018)
This paper introduces Spice, a system for building verifiable state machines (VSMs). A VSM is a request-processing service that produces proofs establishing that requests were executed correctly according to a specification. Such proofs are succinct (a verifier can check them efficiently without reexecution) and zero-knowledge (a verifier learns nothing about the content of the requests, responses, or the internal state of the service). Recent systems for proving the correct execution of stateful computations—Pantry, Geppetto, CTV, vSQL, etc.–implicitly implement VSMs, but they incur prohibitive costs. Spice reduces these costs significantly with a new storage primitive. More notably, Spice’s storage primitive supports multiple writers, making Spice the first system that can succinctly prove the correct execution of concurrent services. We find that Spice running on a cluster of 16 servers achieves 488–1167 transactions/second for a variety of applications including inter-bank transactions, cloud-hosted ledgers, and dark pools. This represents an 18,000–685,000× higher throughput than prior work.